2015
DOI: 10.1186/s12879-015-1189-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a birth cohort study dedicated to assessing acute infections using symptom diaries and parental collection of biomaterials

Abstract: BackgroundA birth cohort dedicated to studying infections in early childhood may be assisted by parental recording of symptoms on a daily basis and a collection of biomaterials. We aimed at testing the feasibility of this approach for use in a long-term study focusing on infections in children in Germany.MethodsParents of 1- to 3-year-old children (n = 75) were recruited in nursery schools. They were asked to complete a symptom diary on a daily basis and to take monthly and symptom-triggered nasal swabs and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…The non-finding rate in community-based studies with nasal swabbing of children with respiratory symptoms lies between one quarter and one third. 5,17,23 Furthermore, Kusel 6 et al also found viruses in 24.6% of samples obtained on days without symptoms. 23 Here the question arises if this still would be considered as an infection.…”
Section: Discussionmentioning
confidence: 95%
“…The non-finding rate in community-based studies with nasal swabbing of children with respiratory symptoms lies between one quarter and one third. 5,17,23 Furthermore, Kusel 6 et al also found viruses in 24.6% of samples obtained on days without symptoms. 23 Here the question arises if this still would be considered as an infection.…”
Section: Discussionmentioning
confidence: 95%
“…The symptom diary was developed based on the symptom diary used by the Australian birth cohort ORChID and adapted according to the results of our feasibility study. 12,13 Participants can choose between a paper-based diary, an online version or an app. Changes between the different modes are allowed.…”
Section: Symptom Diarymentioning
confidence: 99%
“…Our focus is on viruses and we expect prevalence of human respiratory virus and respiratory syncytial virus as well as rotavirus, norovirus and adenovirus. 13 Nevertheless, research on other causative agents of respiratory and gastrointestinal infections is planned or may evolve in future collaborations. Furthermore, all nasal swabs and stool samples will be analysed regarding changes of microbial community composition over time and with respect to influencing factors like infections, vaccinations, antibiotic intake and breastfeeding/nutrition over time.…”
Section: Planned Use Of Collected Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the TEDDY moms who worked and smoked and whose child was an ethnic minority reported fewer RIEs. Several previous studies have suggested that more educated mothers at higher socio‐economic status may be more compliant or attentive to requests to document RIEs in their child leading to higher reports (Bergmann et al, ; Grüber et al, ; Shi et al, ; Simoes, ; Zoch et al, ). Previous studies have also documented that more concerned parents tend to report more RIEs in the child (Andre et al, ; Van Der Gaag & Van Droffelaar, ).…”
Section: Discussionmentioning
confidence: 99%